2006
DOI: 10.1207/s15328015tlm1804_3
|View full text |Cite
|
Sign up to set email alerts
|

Using Structured Debate to Teach a Controversial Topic: Mammography for Women in Their 40s

Abstract: A structured debate resulted in residents reporting increased comfort level and willingness to discuss mammography with women in their 40s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The students in both cohorts thoroughly enjoyed the debate, they were excited and engaged, alongside as seeing it as a valuable learning experience (Dundes, 2001;Helenius et al, 2006). Significantly, and in contrast to some of the previous literature, this paper has found that these students rarely significantly altered their view from their original perspectives (Green & Klug, 1990;Omelicheva & Avedeyeva, 2008;Kennedy, 2009), rather the debate offered an opportunity to develop more nuanced and critical justifications in support of their original opinions.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The students in both cohorts thoroughly enjoyed the debate, they were excited and engaged, alongside as seeing it as a valuable learning experience (Dundes, 2001;Helenius et al, 2006). Significantly, and in contrast to some of the previous literature, this paper has found that these students rarely significantly altered their view from their original perspectives (Green & Klug, 1990;Omelicheva & Avedeyeva, 2008;Kennedy, 2009), rather the debate offered an opportunity to develop more nuanced and critical justifications in support of their original opinions.…”
Section: Resultsmentioning
confidence: 76%
“…This limited use may relate to the criticisms levied against the Socratic debate method, for being too adversarial and combative. Yet, research has indicated the effectiveness of debates in supporting learning in a variety of disciplines including economics, education, history, marketing, medicine, nursing, psychology, sociology and social work (Dundes, 2001;Helenius et al, 2006;Kennedy, 2009;Omelicheva & Avdeyeva, 2008). There is, however, a significant dearth of literature specifically reflecting on the use of debates in teaching geography, despite the range of topics in the discipline which offer potential for such a method.…”
Section: Debates Within Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Controversial topics in medicine can also be taught using structured debates. 11 This can also result in increased comfort level of trainees in discussing certain controversial topics in medicine with their patients. 11 Koklanaris et al have shown higher test score among residents who prepared and participated in a debate as compared to traditional lecture format.…”
Section: Discussionmentioning
confidence: 99%
“…11 This can also result in increased comfort level of trainees in discussing certain controversial topics in medicine with their patients. 11 Koklanaris et al have shown higher test score among residents who prepared and participated in a debate as compared to traditional lecture format. 12 In this study, trainees who prepared and participated in a debate were also shown to retain their knowledge better than those who attended a lecture.…”
Section: Discussionmentioning
confidence: 99%